Characterizing the plasma protein binding profiles of chemistry diversified antisense oligonucleotides in human and mouse plasma using an ultrafiltration method - Yun, Cassandra; Fukami, Kazuki; Shinkyo, Raku; Jiang, Rongrong (Rosa) (Frontiers in Pharmacology, 2025)
IntroductionPlasma protein binding plays a significant role in influencing the pharmacokinetic and pharmacodynamic properties of drugs. This study focuses on examining two pairs of sequence-matched ASOs: phosphorodiamidate morpholino oligomers (PMOs) and 2’-O-methoxyethyl/phosphorothioate (MOE/PS)-modified ASOs, to assess their plasma protein binding profiles.MethodsThe binding of both PMO and MOE/PS-modified ASOs was investigated using an ultrafiltration method combined with hybridization electrochemiluminescence, allowing for the measurement of the unbound fraction (fu) in both mouse and human plasma. To further characterize the interaction between ASOs and plasma proteins, individual binding measurements were taken for five major proteins in human plasma: human serum albumin, α1-acid glycoprotein, human γ-globulin, low-density lipoprotein, and high-density lipoprotein.ResultsThe results showed a notable difference in plasma protein binding between the two types of ASOs, with MOE/PS-modified ASOs exhibiting significantly higher binding compared to PMOs. The fu, plasma values revealed no significant species difference between mouse and human plasma. Additionally, a saturation point for fu, plasma was observed in MOE/PS-modified ASOs at concentrations above 1 μM, whereas PMOs did not show saturation even at concentrations up to 10 μM. Notably, human γ-globulins were found to have a predominant binding affinity for both MOE/PS and PMO ASOs at physiological concentrations, surpassing human serum albumin, the most abundant plasma protein.DiscussionThe results suggest that the chemistries of the ASOs, particularly their modifications, are key determinants of their binding profiles. The study also highlights the important, though previously overlooked, role of human γ-globulins in the plasma protein binding of ASOs. This could have implications for understanding ASO distribution and tissue disposition, which may inform the development and optimization of ASO-based therapies.